2015
DOI: 10.4172/0974-8369.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monacolin K of Red Rice and Glucomannan, Combined with a Low Calorie Diet, in Treatment of Dyslipidemia and Hypertension

Abstract: Alarming increase in incidence of cardiovascular disease is result of a nutrition pattern characterized by an increase in consumption of fats, cholesterol, sugar and other refined carbohydrates, concomitant with low consumption of polyunsaturated fatty acids and fibers. The purpose of this study was to evaluate the efficacy of the monacolin K of red rice and glucomannan, associated with low-calorie diet, on improvement of lipid profile and hypertension, symptoms of metabolic syndrome. In 180 Neapolitan patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, some of the above-mentioned studies on red yeast rice extracts also reported a concurrent decrease in LDL cholesterol alone by about 15% [16], to 20% [14], to 25% [17], and a decrease in LDL levels accompanied by the decrease in homocysteine [16], C-reactive protein and some markers of inflammation and vascular remodeling [15]. A meta-analysis comprising 20 studies reported a clinically and statistically significant reduction of LDL cholesterol by 1.02 mmol/L compared to placebo but concluded that the effect was not different from statin therapy [19].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, some of the above-mentioned studies on red yeast rice extracts also reported a concurrent decrease in LDL cholesterol alone by about 15% [16], to 20% [14], to 25% [17], and a decrease in LDL levels accompanied by the decrease in homocysteine [16], C-reactive protein and some markers of inflammation and vascular remodeling [15]. A meta-analysis comprising 20 studies reported a clinically and statistically significant reduction of LDL cholesterol by 1.02 mmol/L compared to placebo but concluded that the effect was not different from statin therapy [19].…”
Section: Discussionmentioning
confidence: 89%
“…The supplementation with red rice extract was associated with a decrease in total cholesterol of about 10-15% in the following participants: in healthy subjects with hyperlipidemia in combination with diet after eight weeks [13], in patients who did not tolerate statins or other lipidlowering agents during a two-month treatment [14], in moderately hypercholesterolemic subjects taking 10 mg monacolins for 4 weeks [15], and in healthy persons treated for 12 weeks with lower dose of the supplement (3 mg monacolin K) combined with 200 μg folic acid per day [16]. The longest study lasting for 24 weeks in which healthy persons with mild to moderate hypercholesterolemia, and mild hypertension took a supplement containing both red rice (10 mg monacolin K) and fiber glucomannan (3 g per day), combined with a diet, showed a significant reduction in total cholesterol level by 20% [17]. A similar result was shown in 8-to-16-year-old children with familial hypercholesterolemia or familial combined hyperlipidemia, who received a dietary supplement containing 3 mg of monacolins, and 10 mg policosanols once a day for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation